2013
DOI: 10.3390/su5125416
|View full text |Cite
|
Sign up to set email alerts
|

‘Milk is Milk’: Organic Dairy Adoption Decisions and Bounded Rationality

Abstract: Abstract:Bounded rationality is an especially appropriate framework for organic dairy adoption decisions as it recognizes internal and external constraints which are critical in understanding complex farm decision making. Farmers use of, and access to, information is examined using interview data gathered from organic, conventional, managed graziers, and Amish dairy farmers in Southwestern Wisconsin at a time when organic milk prices offered a 50% premium over conventional prices. Focusing on certain aspects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Of the surveyed producers, 54.8% said they did not have a succession plan. These results align with Brock and Barham (2013) where dairy producers also indicated economics to be one of the primary forces behind decision-making. Organic grassfed producers in the current study reported similar drivers for on-farm decision-making, with economics, environmental reasons and health being the major influences.…”
Section: Discussionsupporting
confidence: 89%
“…Of the surveyed producers, 54.8% said they did not have a succession plan. These results align with Brock and Barham (2013) where dairy producers also indicated economics to be one of the primary forces behind decision-making. Organic grassfed producers in the current study reported similar drivers for on-farm decision-making, with economics, environmental reasons and health being the major influences.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies confirm the opinion that farmers with distinctly pro-environmental attitudes are more inclined to act in an environmentally-friendly way and are more likely to adopt organic farming [Best 2010]. The results of studies also indicate the significance of social support for the development of organic production [Brock, Barham 2013]. This social support is now being put on display with the application of new technologies.…”
Section: Resultssupporting
confidence: 54%
“…In fact, lack of knowledge of the benefits derived from converting into organic has been identified as one of the main causes of failure to convert. This lack of information is addressed through the creation of social networks, as observed by researchers using qualitative techniques to study the transition into organic dairy in Southwestern Wisconsin [40].…”
Section: Background On Social Network Analysismentioning
confidence: 99%